Diagnosis dan Kelasifikasi Diabetes Mellitus - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
This paper presented the main recommendations for the definition and classification.of diabetes mellitus and of impaired glucose intolerance in non-pregnant adults.Diabetes mellitus is not a disease in the classical sense but is more probably a syndrome best characterized as a state of chronic hyperglycemia of various etiology. It may present with acute symptoms that include polyuria, polydipsia and unexplained weight loss and these can progress to life threatening ketoacidosis or hyperosmolar coma. Chronic hyperglycemia may be asymptomatic, but it has long been recognized as a predisposing factor for specific microvascular complications, namely neuropathy, retinopathy and nephropachy.Blood glucose concentration is the most common, variable used to define diabetes mellitus, but the increased blood glucose is not the sole pathological manifestation, nor has it been proved beyond doubt to be first in the pathological sequence. The limit between physiological and pathological values of blood glucose concentration is still debatable. An area of particular difficulty is the evaluation of situation that are near the physiological limit.New criteria for the diagnosis of diabetes mellitus and other catagories of glucose intolerance have been developed by National Diabetes Data Group (1979) and these have been endorsed by World Health Organization in 1980 and revised in 1985.Key Words: diabetes mellitus — target screening — chronic hyperglycemia — glucose intolerance -- hyperosmolar coma